Responsabilidad social corporativa en el sector eléctrico (2011)
In recent years, corporate social responsibility has become a key factor in business management. Thus, new principles and business practices have emerged to ensure sustainable development, taking into account the environmental and social problems. In this respect, the purpose of this paper is to analyze the voluntary information disclosure by the electricity sector´s companies in their corporate social responsibility reports. Given that the main impacts of electrical energy production affects the environment, the analysis of an international sample composed of 40 electrical corporations reveals that sector improvements in environmental performance are superior to the economic and social development